On the recursive sequence x(n+1)=(x(n-(4k+3)))/(1+∏(t=0-2(x(n-(k+1)t-k)))) - Simsek, D.; Abdullayev, F. (Український математичний вісник, 2016)
In this paper a solution of some difference equation was investigated.